Iodonium Metathesis Reactions1. Issue 36 (14th July 2014) - Kasahara, Takahito; Jang, Young Jin; Racicot, Léanne; Panagopoulos, Dimitrios; Liang, Steven H.; Ciufolini, Marco A.
Abstract A metathesis reaction occurs when a diaryliodonium triflate is heated with an aryl iodide, resulting in the formation of a new diaryliodonium triflate.